Cross-frequency coupling in psychiatric disorders: A systematic review. (July 2022) - Yakubov, Boris; Das, Sushmit; Zomorrodi, Reza; Blumberger, Daniel M.; Enticott, Peter G.; Kirkovski, Melissa; Rajji, Tarek K.; Desarkar, Pushpal
Abstract: Cross-frequency coupling (CFC), an electrophysiologically derived measure of oscillatory coupling in the brain, is believed to play a critical role in neuronal computation, learning and communication. It has received much recent attention in the study of both health and disease. We searched for literature that studied CFC during resting state and task-related activities during electroencephalography and magnetoencephalography in psychiatric disorders. Thirty-eight studies were identified, which included attention-deficit hyperactivity disorder, Alzheimer's dementia, autism spectrum disorder, bipolar disorder, depression, obsessive compulsive disorder, social anxiety disorder and schizophrenia. The systematic review was registered with PROSPERO (ID#CRD42021224188). The current review indicates measurable differences exist between CFC in disease states vs. healthy controls. There was variance in CFC at different regions of the brain within the same psychiatric disorders, perhaps this could be explained by the mechanisms and functionality of CFC. There was heterogeneity in methodologies used, which may lead to spurious CFC analyses. Going forward, standardized methodologies need to be established and utilized in further research to understand the neuropathophysiology associated with psychiatric disorders. Highlights: Cross-frequency Coupling (CFC) in the brain plays a critical role in neural computation, learning and communication. We identified relationships between CFC findings and clinical characteristics, cognition and treatment outcomes. There is significant measurable differences between CFC in disease states vs. healthy controls. A significant heterogeneity in methodology used was noticed. Going forward, standardized methodologies need to be established.